IMPLEMENTASI KEADILAN RESTORATIF TERHADAP PENYELESAIAN TINDAK PIDANA PENCURIAN DALAM LINGKUP KELUARGA DI KEJAKSAAN - Kadek Putra Yasa; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Jurnal Ilmu Hukum Sui Generis, 2023)
This study aims to investigate the implementation of Restorative Justice in accordance with the Regulation of the Republic of Indonesia's Prosecutor's Office Number 15 of 2020 concerning Discontinuation of Prosecution Based on Restorative Justice in cases of theft within the family scope handled by the Buleleng District Prosecutor's Office. Restorative Justice is an alternative approach to conflict resolution that focuses on relationship restoration and social recovery through active participation of all parties involved. The research method used in this study is empirical legal research. The study aims to analyze the implementation, obstacles, and efforts made by the Buleleng District Prosecutor's Office in handling theft cases resolved through Restorative Justice. The results of this study indicate that the process of implementing Restorative Justice in theft cases within the family scope handled by the Public Prosecutor in the Buleleng District Prosecutor's Office, although encountering obstacles or challenges, has been carried out well in terms of procedural aspects. However, not all criminal cases can be resolved through Restorative Justice; there are conditions that must be met in accordance with the Regulation of the Republic of Indonesia's Prosecutor's Office Number 15 of 2020 concerning Discontinuation of Prosecution Based on Restorative Justice